STU Enterprise: Sambal Yummy / Muhammad Anas Zamzuri ... [et al.] - Zamzuri, Muhammad Anas; Md Juhari, Farah Najiha; Zainal, Rohzaiana; Saat, Fatin Syahirah (2021)
This assignment's purpose is stated in terms of BMC's purpose. The objective at sight is to make it clear that BMC is a page dedicated to the most critical aspects of our startup. The BMC is also straightforward and concise. The business model is a plan that identifies our company at its inception and later helps us build it. It allows us to communicate easily with our team, investors, partners, and even staff in order to achieve our goals. BMC also highlights the client's expectations. A business model's canvas forces you to think beyond your product. The business becomes evident when you imagine how you'll sell your product, what resources you'll require, and which consumer groups you'll be able to serve. Last but not least, the BMC informs us on how to minimize the risk of failure. The business model canvas assists you in completing the processes necessary to bring your idea to market. This shows the effectiveness of the BMC in forcing us to find and produce a solution in preventing us from continuing to receive failure that can dishearten us in the business world.